Effect of Chitosan on Chlorophyll Content and Phytotoxicity in Brassica Juncea L. - Sulistia Ningsih; Dahlia Wulan Sari (Universitas Khairun, 2023)
The positive impact of chitosan has been widespread and has attracted interest from farmers with the pretext that it is safe for the environment. However, information on the adverse effects of using chitosan on plants still needs to be available. This study aims to discover the side effects of applying chitosan on the Brassica juncea. This test is done using Complete Random Design (CRD). The test is carried out by applying a solution of chitosan with five series of concentrations (0.5%, 1.5%, 2.5%, 3.5%, and 4.5%) plus control of acetic acid 1% (AA) to the upper and lower surfaces of the B. juncea leaves (old and young leaves) using a brush smooth to drip wet. The trial was repeated four times. Data was analyzed using ANOVA (Analisis of Variance). When there is a significant difference between the treatments, further tests are conducted using DMRT at a substantial level of 5%. In two week and three week B. juncea plant, the highest chlorophyll content is observed in the chitosan with a concentration of 3.5% and 0.5% with the same value of 0.74 mg/g, while the lowest concentration is at 1.5% 0.61 mg/g at the age of two weeks and 0.50 mg/g at three weeks. Using chitosan at high concentrations (2.5-4.5%) indicates phytotoxic occurrence in the leaves of two week or three week old B. juncea plants. Phytoxic indications are seen in rolling leaves, thickening, and structurally more hardinge when compared with low concentration (0.5% and 1.5%) and control treatments. It is best to pay attention to the use of concentrations of chitosan so that plants get optimal positive effects without causing adverse side effects.